ANALYSIS OF THE USE OF CODE MIXING BETWEEN THAI AND ENGLISH LANGUAGE IN FACEBOOK - Khusainee Hahyesalaemae (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2017)
The thesis is mainly the use of code mixing between Thai and English language in social media networking (Facebook) by Thai Youngers. Code mixing is mixing two or more languages and only the change some of elements such as word and phrase in a sentence and usually happens in informal situation and mixing two languages or more languages in one situation. The researcher wants to analyze the use of code mixing by Thai Youngers in social media networking especially Facebook because the researcher wants to know the kinds, the forms, and the reasons of using code mixing by Thai Youngers as users. The technique of collecting the data is observation and documentation. The researcher used qualitative observation because the researcher needs to observe the language behaviors; code mixing by Thai Youngers account. The samples of this study are thirty Thai Youngers. The results of this study shows 1) the kinds of code mixing, 2) the forms of code mixing, and 3) the reasons of code mixing used by Thai Youngers. There are three kinds of code-mixing used by Thai Youngers in Facebook; words insertion, phrase insertion, and hybrid. There are two forms of code-mixing; code mixing in the form word and code mixing in the form phrase used by Thai Youngers in social media networking (Facebook). The researcher found five reasons of code mixing that consist of (a) showing personal habit, (b) matching with the situation, (c) conveniences, (d) making more simple and familiar, and (e) following the trend.